2000
DOI: 10.1211/0022357001774552
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Iron(III) Chitosan Intake on the Reduction of Serum Phosphorus in Rats

Abstract: Because of the widespread use of aluminium- and calcium-containing phosphate binders for the control of hyperphosphataemia in patients with end-stage renal failure, an iron(III) chitosan complex was synthesised and fed to rats to measure its effect on serum phosphorus and calcium, intestinal phosphate binding and phosphate absorption. Thirty-six Wistar rats were randomly selected and distributed into a baseline group (n = 6), a control group (n = 8 (days 0-15), n = 8 (days 16-30)) and a treatment group (n = 8 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
3

Year Published

2002
2002
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 38 publications
1
13
3
Order By: Relevance
“…These results are different from those reported by Baxter et al. [1], which reported a significant difference between serum iron concentration in normal rats fed with chow containing iron chitosan complex (1% w/w) (treated group) over a 30‐day period and the control group fed with normal chow. Hsu et al.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These results are different from those reported by Baxter et al. [1], which reported a significant difference between serum iron concentration in normal rats fed with chow containing iron chitosan complex (1% w/w) (treated group) over a 30‐day period and the control group fed with normal chow. Hsu et al.…”
Section: Discussioncontrasting
confidence: 99%
“…Thus, the chemical cross-linking of chitosan with glutaraldehyde occurs by a Shiff's reaction on aldehyde groups on glutaradehyde with a free amine group from chitosan that results in the insolubility of polymer in acid pH (stomach) and consequent release of the iron of polymer into the circulating blood. These results are different from those reported by Baxter et al [1], which reported a significant difference between serum iron concentration in normal rats fed with chow containing iron chitosan complex (1% w ⁄ w) (treated group) over a 30-day period and the control group fed with normal chow. Hsu et al also showed an increase of 60% in serum iron concentration in azotemic rats fed with a diet supplemented with ferric citrate (4% w ⁄ w) after 30 days [8].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…CH‐FeCl combines the chelation properties of chitosan and iron, without the risk of increased iron availability and consequent toxicity. This compound has been shown to reduce phosphate absorption in the intestine of diabetic rats with hyperphosphataemia induced by diet phosphorus overload . However, in those studies, the animals did not have CKD or CKD‐MBD, which limits the clinical usefulness of the results.…”
mentioning
confidence: 99%